PENGARUH NPM, DER, TATO DAN CR TERHADAP PERTUMBUHAN LABA - Athira Athira; Murtanto Murtanto (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The purpose of writing this thesis is to examine the effect of Net Profit Margin, Debt to Equity Ratio, Total Asset Turnover and Current Ratio on Profit Growth in Hotel, Restaurant and Tourism Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 Period. The researcher uses quantitative research methods and the analytical technique used in this research is multiple linear regression analysis. Sampling using the saturated technique amounted to 67 with a population of 35 companies during the 2019-2021 period. The results showed: (1) Net Profit Margin had no effect on profit growth. (2) Debt to Equity Ratio has no effect on profit growth. (3) Total Asset Turnover has a positive and significant effect on profit growth. (4) Current Ratio has no effect on profit growth.